Nanofiber sensor for detecting Cu < 2 + > as well as preparation method and application of nanofiber sensor
Through the electrospinning technology of 1,4-DHAQ@GEL-PCL nanofiber membrane, fluorescence quenching is achieved by reacting 1,4-dihydroxyanthraquinone with Cu2+, which solves the problem of insufficient sensitivity for copper ion detection in industrial wastewater. It has a simple and convenient high sensitivity detection method, suitable for industrial wastewater treatment.
Patent Information
- Application Number
- CN202411218430.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-20
AI Technical Summary
The existing heavy metal ion detection methods are not sensitive enough to detect copper ion in industrial wastewater, and the detection process is complex, expensive and long time. The linear detection range of existing solid-state fluorescence sensors is not sufficient to adapt to the high concentration of copper in industrial wastewater. ion.
The 1,4-DHAQ@GEL-PCL nanofiber membrane was used as a solid-state fluorescence sensor, and prepared by electrospinning technology. The reaction of 1,4-dihydroxyanthraquinone and Cu2+ caused fluorescence quenching, achieving high sensitivity to Cu2+ in water Testing, and the preparation process is simple and easy to operate.
It realizes fast, accurate and high-sensitivity detection of copper ions in wastewater, is suitable for large-scale sample analysis, and has good sensor stability and ionic interference resistance, which is suitable for industrial wastewater treatment.
Smart Images

Figure CN119162737A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material chemistry and sewage detection, and specifically relates to a method for detecting Cu 2+ Nanofibers and their applications. Background Art
[0002] The disclosure of this background information is intended to enhance understanding of the general background of the invention and should not necessarily be taken as an acknowledgment or any form of suggestion that this information constitutes the prior art already known to a person skilled in the art.
[0003] The rapid development of industrialization has led to the generation of a large amount of industrial wastewater, which usually contains a variety of harmful heavy metal ions, such as Cr 3+ , Pb 2+ , Cu 2+ 、Co 2+ The main factors causing this pollution include leather tanning, electroplating, mining and textile manufacturing industries. These heavy metals pose a serious threat to human health and the environment. Copper is an essential trace element for the human body and can form biologically active substances such as proteins and various enzymes with organic compounds in the body. However, high concentrations of Cu 2+ The content will burden human organs, causing liver cirrhosis, ascites and even worse. Copper pollution in the environment not only reduces the quality of the water environment, but also affects the balanced and stable development of plants, animals, microorganisms, etc. in the water, threatening the quality and safety of aquatic products. Therefore, it is very important to detect heavy metal ions in wastewater in a real-time, efficient and environmentally friendly manner.
[0004] Fluorescence sensor technology offers a promising alternative due to its high sensitivity, simplicity, and cost-effectiveness. Fluorescence sensors can provide real-time monitoring and immediate results, which are essential for timely decision-making in industrial processes. For industrial wastewater, due to the diversity of industrial types and process flows, the types and concentrations of heavy metal ions contained in the wastewater produced are also different. In addition to their complex composition, large quantity and volume, they also have the characteristics of unstable water quality and water volume. In addition, most of the existing heavy metal ion detection methods require complex pretreatment, and have the disadvantages of high detection costs, long detection time, and complex operation. At present, many scholars are developing new ion detection technologies, but liquid detection reagents are inconvenient to carry, cumbersome to prepare, and have harsh storage conditions. The development of solid-state fluorescence sensors has improved the portability and ease of use of fluorescence.
[0005] Electrospinning technology offers significant advantages for producing nanofibers as substrates for fluorescent sensors. This technology uses high-voltage electric fields to produce fine fibers with diameters ranging from nanometers to micrometers through polymer solutions. The resulting nanofibers have several beneficial properties, including high surface area, high porosity, and enhanced interactions between fluorescent detectors and target ions, thereby improving sensor sensitivity and detection limits. In addition, the porosity of electrospun nanofibers facilitates efficient mass transfer, resulting in rapid responses when detecting ions in aqueous solutions. Electrospinning is also versatile and applicable to a wide range of polymers and composites, which allows the properties of nanofibers to be customized to meet specific detection needs. Therefore, electrospinning technology is ideal for integrating fluorescent sensor technology into the development of new materials.
[0006] Wang Meiling et al. (2011) proposed a substrate made of cellulose acetate by electrospinning for the preparation of a solid-state fluorescent sensor for detecting copper ions. However, its linear detection range was only 2.5× 10 -9 to 3.75 × 10 -8 M. The copper ion content in industrial wastewater is generally 10 -6 M order of magnitude, it is not suitable for detecting copper ions in industrial wastewater. Therefore, it is necessary to develop a method with simple operation, accurate detection results and high sensitivity to achieve rapid qualitative and quantitative detection and analysis of heavy metal ions in wastewater solutions. Summary of the invention
[0007] In view of the current lack of solid sensors for detecting copper ions in wastewater, the present invention provides a method for detecting Cu 2+ The nanofibers can achieve rapid detection of copper ions in wastewater with high sensitivity and high stability.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned nanofibers, which can be completed in just one step, with green and environmentally friendly raw materials, economical and easily available, and a simple processing process.
[0009] Another object of the present invention is to provide a method for detecting copper ions in wastewater using the above-mentioned nanofibers, which is simple to operate, convenient to carry, has a short detection process, and is suitable for rapid detection and analysis of large quantities of samples to be tested.
[0010] To achieve the above purpose, the present invention adopts the following technical solution.
[0011] A method for preparing a 1,4-DHAQ@GEL-PCL nanofiber membrane comprises the following steps: (1) Dissolving gelatin (GEL) and polycaprolactone (PCL) in an organic solvent to obtain a base solution; (2) 1,4-dihydroxyanthraquinone (1,4-DHAQ) was added to the base liquid and electrospun to obtain 1,4-DHAQ@GEL-PCL nanofiber membrane.
[0012] The mass ratio of gelatin to polycaprolactone is 4:1-1:4, preferably 4:3.
[0013] The organic solvent is selected from at least one of formic acid, acetic acid and chloroform; preferably a mixed solvent of formic acid and acetic acid in a volume ratio of 1:3-3:1.
[0014] The mass fraction of gelatin and polycaprolactone in the base liquid is not less than 28%, preferably 28%-37%, and more preferably 31%-37%.
[0015] The concentration of the 1,4-dihydroxyanthraquinone in the base liquid is a saturated solution.
[0016] The electrospinning parameters are: voltage 15 kV-20 kV, injection rate 0.1 mm / min, receiver distance 15 cm, and time 2 hours-5 hours.
[0017] A 1,4-DHAQ@GEL-PCL nanofiber membrane obtained by the above preparation method.
[0018] The above nanofiber membrane can be used to prepare solid-state fluorescent sensors for detecting Cu in water. 2+ .
[0019] A method for detecting Cu in water 2+ The method comprises the following steps: S1. contacting the above-mentioned 1,4-DHAQ@GEL-PCL nanofiber membrane or solid-state fluorescent sensor with the water body to be tested; S2. Compare the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step S1 with that of the nanofiber membrane or solid-state fluorescence sensor that is not in contact with the water body. A decrease in fluorescence intensity indicates that the water body contains Cu 2+ .
[0020] A quantitative detection method for Cu in water 2+ The method comprises the following steps: s1. The above 1,4-DHAQ@GEL-PCL nanofiber membrane or solid-state fluorescent sensor was respectively mixed with a series of concentrations of Cu 2+ The solution comes into contact with the water to be tested; s2, detect the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step s1, and establish a series of concentrations of Cu 2+ Cu in solution 2+ Functional relationship between molar concentration and fluorescence intensity; s3. Calculate Cu by the fluorescence intensity of the water to be tested 2+ concentration.
[0021] Preferably, the contact time is not less than 1 min; preferably not less than 5 min.
[0022] The excitation wavelength of the fluorescence intensity detection is 400 nm, and the detection wavelength is 500 nm-515 nm or 506 nm.
[0023] The mechanism of the present invention is as follows: The 1,4-DHAQ@GEL-PCL nanofiber fluorescence sensor provided by the present invention is doped with 1,4-DHAQ for qualitative and quantitative detection of Cu in aqueous solution 2+ 1,4-DHAQ carries -OH auxochromophore, which makes 1,4-DHAQ itself appear orange-red and has a certain fluorescence effect. Under normal temperature conditions, the structure of the unsaturated ketone contained in it is similar to Cu 2+ A reaction occurs to generate copper-containing phenolate, and fluorescence quenching occurs. The reaction formula is as follows: ; The change of fluorescence can be measured by fluorescence spectrophotometer. The weakening of fluorescence intensity indicates that the detection system contains Cu 2+ .
[0024] The present invention has the following advantages: The nanofiber membrane prepared by the present invention can be completed in one step. The raw materials are green, environmentally friendly, economical and easy to obtain, and the processing process is simple. It can maintain its original performance and be stored for six months at room temperature and away from light. The incubation time of the prepared fluorescent sensor is 5 minutes, which is suitable for rapid detection and analysis of large quantities of samples to be tested, and has high sensitivity and good stability. The prepared fluorescent sensor solid sensor is simple to operate and easy to carry. The present invention solves the problem of the current lack of solid sensors for detecting copper ions in wastewater, and the sensor is resistant to interference from various ions, has good specificity, and is suitable for various wastewater treatment fields for detecting Cu ions. 2+ Detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the preparation and detection process of the solid-state fluorescence sensor; Figure 2 The SEM images of 1,4-DHAQ@GEL-PCL nanofibers prepared with different contents of base solution; AE are base solutions with mass fractions of 25.08%, 28.08%, 31.09%, 33.96%, and 36.94%, respectively; Figure 3 is a SEM image of 1,4-DHAQ@GEL-PCL nanofibers prepared in Example 2; Figure 4 is the distribution diagram of nanofiber diameter in Gaussian fitting Example 2; Figure 5 is the fluorescence intensity of the sensor at different incubation times; Figure 6 is the fluorescence intensity of the solid-state fluorescence sensor after being impregnated with different metal cations; Figure 7 Different concentrations of Cu 2+ Fluorescence intensity of the solid-state fluorescence sensor after treatment; Figure 8 Solid-state fluorescent sensor for Cu 2+ Linear fit plot of the concentration detection range. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing a 1,4-DHAQ@GEL-PCL nanofiber membrane, comprising the following steps: (1) Dissolving gelatin (GEL) and polycaprolactone (PCL) in an organic solvent to obtain a base solution; (2) 1,4-dihydroxyanthraquinone (1,4-DHAQ) was added to the base liquid and electrospun to obtain 1,4-DHAQ@GEL-PCL nanofiber membrane.
[0027] GEL has good hydrophilicity but poor mechanical properties, PCL has good mechanical properties and ductility but poor hydrophilicity and is insoluble in water. The electrospun nanofiber membrane of pure GEL has poor mechanical properties, is easy to break and is not conducive to storage. It is easy to combine with water in the air and swell. On the contrary, the electrospun product of pure PCL has poor hydrophilicity and is not conducive to application in aqueous solution. Combining the characteristics of the two substrate materials, when the mass ratio of GEL and PCL is 4:1-1:4, such as 4:1, 4:2, 4:3, 4:4, 3:4, 2:4, 1:4, the prepared electrospun nanofibers have certain mechanical properties and are more conducive to detection in aqueous solution.
[0028] The organic solvent is at least one of formic acid, acetic acid and chloroform; in order to make the fiber thinner and more uniform and obtain a larger specific surface area, the organic solvent is a mixture of formic acid and acetic acid; preferably, the volume ratio of formic acid to acetic acid is 1:3-3:1, such as 1:3, 1:1, 3:1.
[0029] The solubility of 1,4-DHAQ in the base solution is limited. Since the nanofiber membrane is based on the fluorescence change caused by the reaction of 1,4-DHAQ with copper ions, in order to improve the detection sensitivity and detection limit of the fiber membrane, a saturated solution is generally selected. The detection limit of the nanofiber membrane can also be adjusted by adjusting the concentration of 1,4-DHAQ in the base solution.
[0030] The parameters of electrospinning will affect the morphology of the nanofiber membrane, and thus affect its detection performance: for example, the voltage mainly affects the process of electrospinning to form nanofibers. When the voltage is low, the electric field force on the substrate liquid after it is ejected during the spinning process is small, the fiber stretching and extension effect is poor, and the formed nanofibers adhere to each other, which reduces the specific surface area of the nanofiber membrane and the ability to capture and detect metal ions. A voltage of 15kV-20kV can be selected as the preparation condition to prepare nanofiber membranes that are independent and non-adhesive. For example, the mass fraction of the substrate liquid mainly affects the quality of the electrospinning product. Within a certain concentration range, as the mass fraction of the solute in the electrospinning liquid increases, the electrospinning product gradually becomes uniform and stable. This is because GEL and PCL are both polymer materials, which can increase the viscosity of the electrospinning liquid after being fully dissolved. The high viscosity enables the formation of a continuous and stable Taylor cone during the electrospinning process, which increases the strength of the fiber itself during formation, so that it will not break and fuse to form beads when stretched and extended to form nanofibers, and then deposit on the receiver to obtain uniform nanofibers. When the mass fraction is lower than 28%, only a few continuous nanofibers can be formed in the electrospinning product, accompanied by a large number of beads and droplets interspersed between the nanofibers, the nanofiber diameter is uneven, and the fibers are adhered and lumped; when the mass fraction is greater than 34%, a large number of nanofibers can be clearly observed in the electrospinning product, and the nanofiber diameter is also increased, but the formed nanofibers are bent and folded, the diameter distribution is uneven, and they do not have the best nanofiber morphology. When the mass fraction is 34%, it can be observed that a large number of independent, smooth, and straight nanofibers are formed in the state of fresh preparation and spinning, and a well-formed 1,4-DHAQ@GEL-PCL nanofiber fluorescence sensor can be prepared. If the fiber morphology is unstable, the difference in fiber diameter will be large, the specific surface area will be unstable, and the amount of 1,4-DHAQ carried will not be fixed. In actual detection applications, materials with different fiber morphologies can detect Cu because of the presence of 1,4-DHAQ. 2+ , but it is difficult to obtain a stable linear range relationship between fluorescence intensity and ion concentration. For example, the longer the electrospinning preparation time, the more nanofibers are produced, the more 1,4-DHAQ can be carried, and the thickness is also greater. The content of 1,4-DHAQ affects ion detection. In addition, the fiber membrane is thin and has low strength and is easy to break if the preparation time is short. Therefore, the appropriate electrospinning time can be selected according to the specific application scenario.
[0031] A 1,4-DHAQ@GEL-PCL nanofiber membrane obtained by the above preparation method.
[0032] The above nanofiber membrane can be used to prepare solid-state fluorescent sensors for detecting Cu 2+ .
[0033] The present invention also provides a method for detecting Cu in water by using the nanofiber membrane or solid-state fluorescent sensor. 2+ The method comprises the following steps: S1. contacting the above-mentioned 1,4-DHAQ@GEL-PCL nanofiber membrane or solid-state fluorescent sensor with the water body to be tested; S2. Compare the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step S1 with that of the nanofiber membrane or solid-state fluorescence sensor that is not in contact with the water body. A decrease in fluorescence intensity indicates that the water body contains Cu 2+ .
[0034] The contact time with water can be determined according to the Cu content in water. 2+ The concentration is adjusted. When the Cu 2+ When the concentration is low, the contact time can be extended to reach Cu 2+ Full contact with 1,4-DHAQ. Generally, the time is not less than 5 minutes. 2+ When the ion content is very high, such as above 10 −4 M, the contact time can be reduced; however, too short a contact time, such as less than 1 min, is likely to cause greater errors, so you can choose to dilute the sample to be tested.
[0035] The fluorescence intensity was detected with an excitation wavelength of 400 nm and within the range of 500 nm to 515 nm. 2+ A linear quantitative relationship can be established between molar concentration and fluorescence intensity, which can be used to determine the concentration of Cu in water. 2+ Concentration determination, especially with a strong fluorescence emission peak around 506 nm, can be used for more sensitive quantification.
[0036] In some embodiments, in order to 2+ The quantitative detection includes the following steps: s1. The above 1,4-DHAQ@GEL-PCL nanofiber membrane or solid-state fluorescent sensor was respectively mixed with a series of concentrations of Cu 2+ The solution comes into contact with the water to be tested; s2, detect the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step s1, and establish a series of concentrations of Cu 2+ Cu in solution 2+ Functional relationship between molar concentration and fluorescence intensity; s3. Calculate Cu by the fluorescence intensity of the water to be tested 2+ concentration.
[0037] The present invention is further described below in conjunction with the examples and drawings, but the present invention is not limited by the following examples. Unless otherwise specified, the reagents in the examples are all commercially available products of analytical grade.
[0038] Example 1 Preparation of 1,4-DHAQ@GEL-PCL nanofiber membrane (1) GEL and PCL (CAS 24980-41-4, average Mn 45000) with a mass ratio of 4:3 were dissolved in a formic acid / acetic acid mixed solvent with a volume ratio of 3:1 to obtain base solutions with mass fractions of 25.08%, 28.08%, 31.09%, 33.96%, and 36.94%; (2) adding 1,4-DHAQ to the above-mentioned base solution to a mass fraction of 0.1%, and dissolving by ultrasonication to obtain a spinning solution; (3) The spinning solution was loaded into the syringe and the electrospinning parameters were set as follows: voltage 20 kV, injection rate 0.1 mm / min, receiver distance 15 cm, and electrospinning for 4 h to obtain 1,4-DHAQ@GEL-PCL nanofiber membrane.
[0039] The SEM images of the obtained nanofiber membranes are as follows: Figure 2 As shown in the figure: when the mass fraction is lower than 28%, only a few continuous nanofibers can be formed in the electrospinning product, and there are a large number of beads and droplets interspersed between the nanofibers. The diameter of the nanofibers is uneven, and the fibers are adhered and agglomerated; with the increase of the mass fraction, the diameter of the nanofibers increases, and the adhesion and agglomeration are greatly reduced. When the mass fraction is 34%, it can be observed that a large number of independent, smooth, and straight nanofibers are formed in the state of fresh preparation and spinning, and a well-shaped 1,4-DHAQ@GEL-PCL nanofiber membrane can be prepared; when the mass fraction is greater than 34%, a large number of nanofibers can be clearly observed in the electrospinning product, and the diameter of the nanofibers is also increased, but the formed nanofibers are bent and folded, the diameter distribution begins to become uneven, and the nanofiber morphology is not optimal.
[0040] The 1,4-DHAQ@GEL-PCL was immersed in a 1×10 -4 MCu 2+ The solution was incubated for 3 min and the un-impregnated Cu 2+ The 1,4-DHAQ@GEL-PCL solution was placed on the sample stage of the gel imaging instrument, and the fluorescence image was observed under 312 nm ultraviolet light. It can be seen that the addition of 1,4-DHAQ can significantly enhance the fluorescence of the nanofiber membrane, which is significantly higher than that of the non-impregnated Cu 2+ 1,4-DHAQ@GEL-PCL in solution was immersed in Cu 2+ The fluorescence intensity of 1,4-DHAQ@GEL-PCL after solution was significantly weakened, which was due to the Cu 2+Binding to 1,4-DHAQ changes the chemical structure of the fluorophore, resulting in fluorescence quenching. However, due to differences in the morphology of the fibers, the uniformity of the fluorescence intensity varies.
[0041] The above results show that although the membranes with different fiber morphologies can detect Cu due to the presence of 1,4-DHAQ 2+ The presence of 1,4-DHAQ@GEL-PCL in Cu 2+ It has potential in ion detection; however, in actual detection applications, the fiber diameter varies greatly, which leads to unstable specific surface area and large differences in the amount of 1,4-DHAQ carried, making it difficult to obtain a stable linear range relationship between fluorescence intensity and ion concentration. Therefore, electrospinning under 33.96% conditions was selected to explore the linear range relationship between fluorescence intensity and ion concentration in order to achieve Cu 2+ Quantitative detection of .
[0042] Example 2 1,4-DHAQ@GEL-PCL nanofiber membrane and detection of Cu 2+ Preparation of solid-state fluorescence sensor (1) GEL and PCL (CAS 24980-41-4, average Mn 45000) with a mass ratio of 4:3 were dissolved in a mixed solvent of formic acid / acetic acid with a volume ratio of 3:1 to obtain a base solution with a mass fraction of 34%; (2) adding 1,4-DHAQ to the above-mentioned base solution to a mass fraction of 0.1%, and dissolving by ultrasonication to obtain a spinning solution; (3) The spinning solution was loaded into the syringe and the electrospinning parameters were set as follows: voltage 20 kV, injection rate 0.1 mm / min, receiver distance 15 cm, and electrospinning for 4 h to obtain a 1,4-DHAQ@GEL-PCL nanofiber membrane with a thickness of 0.12 mm.
[0043] The SEM images of the obtained nanofiber membranes are as follows: Figure 3 The fibers are independent and smooth with straight morphology. The diameter of the nanofibers was statistically evaluated using NanoMeasurer 1.2 ( Figure 4 ), 50 nanofibers were randomly selected as samples for measuring diameter, and the Gaussian fitting results showed that the nanofiber diameter was 296.04±14.42 nm.
[0044] Each of the nanofibers prepared above was cut into 1 cm × 4 cm strips to obtain a simple Cu 2+ Solid-state fluorescence sensor.
[0045] Example 3 Solid-state fluorescence sensor for Cu 2+ Detection 1. Effect of incubation time on detection The detection Cu prepared in Example 2 2+ The solid-state fluorescent sensor was immersed in 7 mL of 1×10 -4 MCu 2+ In the ionic solution, the incubation time was set to 1, 2, 3, 4, 5, 6, and 7 minutes (3 parallel samples). After the incubation, the samples were taken out and dried at room temperature. The nanofiber fluorescence sensor was placed on the sample holder of the fluorescence spectrophotometer instrument, and the detection distance of the sample holder was fixed. At an excitation wavelength of 400 nm, the fluorescence intensity in the wavelength range of 450 nm to 550 nm was detected and the results were recorded.
[0046] The fluorescence intensity of the sensor under different pretreatment incubation times is shown in Figure 2. Figure 5 Shown: Immersed in Cu 2+ After the solution was added, the fluorescence intensity of the fluorescent sensor decreased with the passage of time and tended to be stable after 5 minutes. Therefore, 5 minutes was selected as the optimal pretreatment incubation time for the nanofiber fluorescent sensor.
[0047] 2. Selectivity of solid-state fluorescence sensors The solid-state fluorescent sensors were immersed in water with a concentration of 10 −4 Common metal cation nitrate solutions (Mg 2+ 、Al 3+ , K + 、Ni 2+ 、Na + 、Cd 2+ , Hg 2+ 、Co 2+ , Fe 3+ , Fe 2+ Cr 3+ ) and all the above metal cations and Cu 2+ The mixed solution was incubated for 5 minutes. After the incubation, it was taken out and dried at room temperature. The nanofiber fluorescence sensor test strip was placed on the sample holder of the fluorescence spectrophotometer instrument, the detection distance of the sample holder was fixed, and the fluorescence intensity in the wavelength range of 450nm to 550nm was detected at an excitation wavelength of 400nm and the results were recorded.
[0048] The results are as follows Figure 6 As shown in the figure, the solid-state fluorescent sensor prepared by 1,4-DHAQ@GEL-PCL nanofibers is effective for removing Cu 2+ Other ions hardly react, even Cu 2+ Cu can also be detected in the presence of other metal ions 2+ The results of the fluorescence quenching reaction of 1,4-DHAQ@GEL-PCL proved that the fluorescence sensor is sensitive to Cu 2+It has good selectivity and can be used to selectively detect Cu in sample solutions. 2+ .
[0049] 3. Linear relationship range Cu will be detected 2+ Solid-state fluorescent sensors were immersed in 7 mL of Cu 2+ Ionic solution (4.8×10 -6 -6.5×10 -6 M) and incubated for 5 min (3 parallel samples). After the incubation, take out and dry at room temperature, place the nanofiber fluorescence sensor on the sample holder of the fluorescence spectrophotometer instrument, fix the detection distance of the sample holder, detect the fluorescence intensity in the wavelength range of 450 nm to 550 nm under the excitation wavelength of 400 nm, and record the result of 506 nm wavelength.
[0050] Different concentrations of Cu 2+ The fluorescence intensity of the solid-state fluorescence sensor after treatment is as follows Figure 7 As shown, the solid-state fluorescent sensor for Cu 2+ The linear fitting diagram of the concentration detection range is shown in Figure 8 As shown. It can be seen that when Cu 2+ The concentration is 4.8×10 -6 -6.5×10 -6 M, the fluorescence intensity of the fluorescent sensor is similar to that of Cu 2+ The concentration shows a good linear relationship, and the corresponding mathematical model is: I 1=-56.49 [Cu 2+ ] + 1012.72, indicating that the sensor can achieve Cu 2+ Quantitative detection of ions.
[0051] 4. Sensor Storage Period The detection Cu prepared in Example 4 2+ The solid-state fluorescent sensor was stored at room temperature and away from light for six months. After being taken out, five samples containing Cu were randomly tested according to the method of Example 3. 2+ Solution samples of unknown concentration were tested by ICP-MS for comparison and verification.
[0052] Table 1 Comparison of the nanofiber fluorescence sensor and ICP-MS test results after six months of storage (×10 -6 M) The comparison and verification of the solid-state fluorescence sensor test results and the ICP-MS test results are shown in Table 1. It can be seen that the solid-state fluorescence sensor prepared by 1,4-DHAQ@GEL-PCL nanofiber membrane stored for six months is still reliable and does not affect the test results.
[0053] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for preparing 1,4-DHAQ@GEL-PCL nanofiber membrane, characterized in that: The following steps are involved: (1) Dissolving gelatin and polycaprolactone in an organic solvent to obtain a base solution; (2) 1,4-dihydroxyanthraquinone was added to the base liquid and electrospun to obtain 1,4-DHAQ@GEL-PCL nanofiber membrane.
2. The preparation method according to claim 1, characterized in that: The mass ratio of gelatin to polycaprolactone is 4:1-1:4; the organic solvent is selected from at least one of formic acid, acetic acid and chloroform; the mass fraction of gelatin and polycaprolactone in the base liquid is not less than 28%; and the concentration of 1,4-dihydroxyanthraquinone in the base liquid is a saturated solution.
3. The preparation method according to claim 1, characterized in that: The mass ratio of gelatin to polycaprolactone is 4:3; the organic solvent is a mixed solvent of formic acid and acetic acid in a volume ratio of 1:3-3:1; the mass fraction of gelatin and polycaprolactone in the base liquid is 28%-37%, preferably 31%-37%.
4. The preparation method according to claim 1, characterized in that: The electrospinning parameters are: voltage 15 kV-20 kV; injection rate 0.1 mm / min; receiver distance 15 cm; time 2 hours-5 hours.
5. A 1,4-DHAQ@GEL-PCL nanofiber membrane obtained by the preparation method according to any one of claims 1 to 4.
6. A solid-state fluorescent sensor prepared from the nanofiber membrane as claimed in claim 5.
7. A nanofiber membrane as claimed in claim 5 and a solid-state fluorescent sensor as claimed in claim 6 for detecting Cu in water 2+ application.
8. A method for detecting Cu in water 2+ The method is characterized in that The following steps are involved: S1. contacting the 1,4-DHAQ@GEL-PCL nanofiber membrane as described in claim 5 or the solid-state fluorescent sensor as described in claim 6 with a water body to be tested; S2. Compare the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step S1 with that of the nanofiber membrane or solid-state fluorescence sensor that is not in contact with the water body. A decrease in fluorescence intensity indicates that the water body contains Cu 2+ .
9. A quantitative detection method for Cu in water 2+ The method is characterized in that The following steps are involved: s1. The 1,4-DHAQ@GEL-PCL nanofiber membrane as described in claim 5 or the solid-state fluorescent sensor as described in claim 6 are respectively mixed with a series of concentrations of Cu 2+ The solution comes into contact with the water to be tested; s2, detect the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step s1, and establish a series of concentrations of Cu 2+ Cu in solution 2+ Functional relationship between molar concentration and fluorescence intensity; s3. Calculate Cu by the fluorescence intensity of the water to be tested 2+ concentration.
10. The method according to claim 8 or 9, characterized in that: The contact time is not less than 1 min; or not less than 5 min; The excitation wavelength of the fluorescence intensity detection is 400 nm, and the detection wavelength is 500 nm-515 nm or 506 nm.
Citation Information
Patent Citations
Porous membrane mixed by 1,4-dihydroxy anthraquinone and cellulose, preparation method and usage
CN103088554A
CNTs-modified 1,4-dioxyanthraquinone doped cellulose-combined porous membrane and preparation method and application thereof
CN106568751A
Drug-loaded nanofiber as well as preparation method and application thereof
CN110478521A
Gelatin / polyester fiber dressing and preparation method thereof
CN115645592A
Composite nanofiber membrane as well as preparation method and application thereof
CN118161645A
Cited By
A kind of nanofiber membrane for rapid detection of copper ions and its preparation method and application
CN122686329A
